PENGARUH SENAM LANSIA TERHADAP TINGKAT KEMANDIRIAN LANSIA DI PANTI WERDHA PANGESTI LAWANG MALANG - Wahyuni, Lutfi; Gustianti, Ita (JURNAL KEPERAWATAN BINA SEHAT, 2011)
Effect of aging process can cause various problems including the decline in physical abilities that result in increased dependence on others. Elderly exercise is a form of physical exercise as a positive influence on a persons level of physical ability, if done properly and correctly. The research objective is to determine the effect of elderly exercise on the level of independence of elderly in Panti Werdha Pangesti Lawang Malang. The research design is pre-experimental with pre-post test types in one group (one group pre-post test design). Population is all elderly in Panti Werdha Pangesti Lawang Malang for about 63 elderly. Then 26 respondents are taken by using purposive sampling. Independent variable is elderly exercise and the dependent variable is level of independence of elderly. Data collected using the Barthel index observation sheet. Then analized by Wilcoxon Sign Rank Test using SPSS version 17.0. Results showed sig. (2 tailed) (p) (0.000) < α (0.05) = H0 is rejected, meaning that there are effect of elderly exercise on the level of independence of elderly in Panti Werdha Pangesti Lawang Malang. The independence level of elderly is influenced by sex, age, length of stay in panti werdha, and also illness. Elderly exercise is proven could be used as alternative exercise for elderly to increase their level of independence. So that health workers can apply this exercise as regular program for the elderly for at least 3 times a week to increase the independence level of the elderly. Elderly with moderate and severe levels of dependence can do this exercise regularly, while the elderly with mild degree of dependence and independence can still do this exercise to maintain their level of independence.Keywords: elderly exercise, level of independence of elderly